The Function of Translation as a Tool for Intercultural Communication in the Global Age - Melati Amir, Rahma; Syukri, Muhammad (JLE: Journal of Literate of English Education Study Program, 2025)
In an increasingly globalized society, translation plays a vital role in overcoming linguistic and cultural barriers and facilitating effective cross-cultural communication. This article examines translation not only as a linguistic process but also as a form of intercultural mediation that enables the transfer of meaning across diverse cultural contexts. The study aims to explore how translation contributes to global understanding by analyzing major translation theories and practical challenges encountered in academic translation. A qualitative descriptive research methodology was employed to investigate translation as a means of intercultural communication within the context of globalization. This approach is particularly suitable for examining contextual meanings, cultural adaptation strategies, and translation techniques used in intercultural exchanges. Data were collected through document analysis of translated academic texts and supported by insights from professional translators. The findings highlight the importance of translation competence in achieving communicative goals, emphasizing the balance between linguistic equivalence and cultural adaptation. The study concludes that despite advancements in translation technology, human translators remain essential in contexts where cultural sensitivity, contextual understanding, and nuanced interpretation are required to produce accurate and meaningful translations.